Soft tissue sarcoma in children, adolescents and young adults: Outcomes according to compliance with international initial care guidelines. Issue 7 (July 2020) - Collignon, C.; Carton, M.; Brisse, H.J.; Pannier, S.; Gauthier, A.; Sarnacki, S.; Tiléa, B.; Savignoni, A.; Helfre, S.; Philippe-Chomette, P.; Cardoen, L.; Boccara, O.; et al.
Abstract: Background: Outcomes for adults with soft tissue sarcoma are better when managed at referral centers. Care guidelines advise for 5 main criteria: 1-Imaging before biopsy; 2-Tumor biopsy before surgery; 3-Multidiscipinary team discussion (MTD) before biopsy; 4-Biopsy in "expert centers"; 5-Somatic molecular biology feasible. The aim is to describe and assess the prognostic impact of initial management of STS according to the type of referring centers and the number of optimal criteria. Methods: Monocentric retrospective analysis of the management of 127 youths (0–25 years) with localized STS treated from 2006 to 2015. Results: Median age at diagnosis was 9.6 years (range: 025). Overall, only 41% patients had 5/5, 28% 3–4, 31% ≤2. No adequate imaging was performed before surgery/biopsy for 18% patients, no biopsy before treatment for 29%. Patients referred by "expert centers" had higher compliance to guidelines (P = 0.025). Upfront surgery was performed in 59/127 patients. Immediate re-operation was inversely related to the number of criteria (0% when 5 criteria vs. 14% for 3–4, 46% if ≤ 2; P < 0.001). For malignant tumors, outcome was better when 5 criteria were reached: 5 year EFS 90.8% (81.4–100.0%) vs. 71.6 for (60.4–84.9%; ≤4 criteria; p = 0.033), OS 93.6% (85.5–100%) vs. 79.5% (68.9–91.8%; p = 0.11), and LRFFS 90.6% (81.0–100.0) vs. 73.1% (62.0–86.3%; p = 0.047). Conclusion: Less than half of the youths with STS are initially managed according to international guidelines, highlighting the need for better information about optimal management. These results plead for immediate management in reference centers to reduce initial burden of therapy.